Conservative treatment and outcome of upper cervical spine fractures in young children: A STROBE-compliant case series. Issue 13 (2nd April 2021) - Tomaszewski, Ryszard; Sesia, Sergio B.; Studer, Daniel; Rutz, Erich; Mayr, Johannes M.
Abstract : Abstract: Cervical spine (C-spine) fractures in young children are very rare, and little information on treatment modalities and functional, radiographic, and patient-reported outcome exists. In this 2-center, retrospective case series, we assessed subjective and functional mid-term outcomes in children aged ⩽5 years whose C-spine fractures were treated nonoperatively. Between 2000 and 2018, 6 children (median age at injury: 23.5 months; range: 16–31 months) with C1 or C2 injuries were treated with Minerva cast/brace or soft collar brace at 1 of the 2 study centers. Two patients suffered C1 fractures, and 4 patients had lysis of the odontoid synchondrosis. Overall, 3 children had sustained polytrauma. One child died due to the consequences of massive head injury. For the primary outcome parameter, we recorded subjective symptoms such as pain and functional restrictions due to the sequelae of C-spine injuries at follow-up. Based on medical records, we also assessed the causes of injury, diagnostic procedures, treatments and complications, and time to fracture consolidation. Median follow-up of the 5 surviving children was 51 months (range: 36–160 months). At the latest follow-up, 4 of 5 children did not complain of any pain. One child who sustained an open head injury in combination with a subluxation of the odontoid and undisplaced fracture of the massa lateralis reported occasional headache. All patients experienced complete fracture healing and normal range of motion of the cervical spine. Median duration of cast/brace treatment was 8.5 weeks. Fracture healing was confirmed by computed tomography in all patients. All C-spine injuries were managed with either Minerva cast/Halo brace or soft collar brace without complications. In our retrospective case series, nonoperative treatment of atlas fractures and dislocations or subluxations of the odontoid in young children using Minerva casts or prefabricated Halo braces resulted in good subjective and functional outcomes at mid-term. We observed no complications of conservative treatment of C1 and C2 injuries in young children.